2016
DOI: 10.1016/j.jpeds.2016.03.041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breastfeeding on Respiratory Symptoms in Infancy

Abstract: This study shows the risk-specific effect of breastfeeding on respiratory symptoms in early life using the comprehensive time-series approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
3
18
2
Order By: Relevance
“…In our study, breastfeeding was not associated with respiratory infections in infancy. This contrasts with an earlier study of the same cohort [ 16 ] which found a protective effect of breastfeeding but only during the first six months after birth, and mainly in girls, whereas we investigated associations during the whole first year of life for both sexes. Furthermore, N0 2 concentrations were only associated with lower respiratory infections when adjusted for other factors but not with any respiratory symptoms in crude or adjusted models.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…In our study, breastfeeding was not associated with respiratory infections in infancy. This contrasts with an earlier study of the same cohort [ 16 ] which found a protective effect of breastfeeding but only during the first six months after birth, and mainly in girls, whereas we investigated associations during the whole first year of life for both sexes. Furthermore, N0 2 concentrations were only associated with lower respiratory infections when adjusted for other factors but not with any respiratory symptoms in crude or adjusted models.…”
Section: Discussioncontrasting
confidence: 58%
“…The BILD Cohort [ 13 16 ] ( www.bild-cohort.ch ) is an ongoing prospective birth cohort study including unselected infants born after April 1999 in the regions of Bern and Basel, Switzerland. Details of the study design are provided elsewhere [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Breastfeeding reduced the severity of respiratory problems in the first 27 weeks of life (RR 0.70; 95% CI 0.55–0.88) (127) and reduces risks for acute otitis media, non-specific gastroenteritis, lower respiratory tract infections, atopic dermatitis, asthma, obesity, type 1 and 2 diabetes, childhood leukemia, sudden infant death syndrome, and necrotizing enterocolitis (125). The American Academy of Pediatrics recommends exclusive breastfeeding for approximately 6 months, followed by continued breastfeeding with complementary foods for 1 year or longer (128).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, any breastfeeding for at least 6 months decreased the occurrence of asthmatic and allergic symptoms induced by PM 2.5 [63], as well as the adverse effects of NO 2 and benzene on mental development [72]. However, a study conducted in Switzerland showed a higher but nonsignificant negative association between PM 10 and respiratory symptoms among breastfed infants compared with non-breastfed ones [83]. The authors explained that this may be the effect of the chemical contamination of the breastmilk of mothers exposed to air pollution.…”
Section: Findings and Discussionmentioning
confidence: 99%